COVID-19 vaccine acceptance and associated factors in 13 African countries: A systematic review and meta-analysis - Azanaw, Jember; Endalew, Mastewal; Zenbaba, Demisu; Abera, Eshetu; Chattu, Vijay Kumar (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic has severely affected the entire world, especially sub-Saharan Africa. As a result, researchers and government agencies are working to create effective COVID-19 vaccinations. While vaccination campaigns are moving rapidly in high-income nations, COVID-19 is still being ruthlessly revealed in low-income nations. However, this difference is not because of a lack of COVID-19 vaccine but mainly due to reluctance. As a result, this review summarized the data on COVID-19 vaccination adoption and factors related among nations in sub-Saharan Africa. Method: Comprehensive searches were conducted using PubMed, EMBASE, Medline, Web of Science, Google Scholar, and the Cochrane Library databases. The risk of bias and methodological quality of each published article that fit the selection criteria were evaluated using Critical Appraisal Checklist tools. All the statistical analysis was done by STATA 16. Results: This review was based on 29 studies with 26,255 participants from sub-Saharan Africa. Using a random-effects model, the pooled prevalence of COVID-19 vaccine acceptance among study participants was 55.04 % (95 % CI: 47.80-62.27 %), I2 = 99.55 %. Being male [POR = 1.88 (95 % CI: 1.45, 2.44)], having positive attitude towards COVID-19 vaccine [POR = 5.56 (95 % CI: 3.63, 8.51)], having good knowledge in COVID-19 vaccine [POR = 4.61 (95 % CI: 1.24, 8.75)], having government trust [POR = 7.10 (95 % CI: 2.37, 21.32)], and having undergone COVID-19 testing in the past [POR = 4.41 (95% CI: (2.51, 7.75)], were significantly predictor variables. Conclusion: This analysis showed that respondents had a decreased pooled prevalence of COVID-19 vaccination acceptance. Sex, attitude, knowledge, government trust, and COVID-19 testing were statistically significantly correlated characteristics that affected the acceptability of the COVID-19 vaccine. All stakeholders should be actively involved in increasing the uptake of the COVID-19 vaccine and thereby reducing the consequences of COVID-19. The acceptance of the COVID-19 vaccination can be increased by using this conclusion as an indicator for governments, healthcare professionals, and health policymakers in their work on attitude, knowledge, government trust, and COVID-19 testing. Keywords: COVID-19 Vaccine acceptance, associated factors, Systematic review, Meta-analysis, sub-Saharan Africa